Impact of Grandchild Caregiving on African American Grandparents. Issue 1 (2nd January 2017) - Samuel, Preethy S.; Marsack, Christina N.; Johnson, Lisa A.; LeRoy, Barbara W.; Lysack, Catherine L.; Lichtenberg, Peter A.
ABSTRACT: The aim of this study was to describe the context and impact of caregiving for grandchildren with health concerns on grandparents. The study sample comprised 391 African American grandparents aged 55 or older. Logistic regression analysis indicated that grandparent caregivers of grandchildren with psychiatric or behavioral problems were more likely to experience a negative impact on their health ( AOR = 7.86, p =.008) and leisure ( AOR = 14.31, p =.024) than grandparent caregivers of grandchildren with no or other types of health problems. The findings underscore the need to support African American grandparent caregivers, particularly those raising grandchildren with mental health problems.